2019
DOI: 10.3847/1538-4357/ab13a0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Particle-in-cell Simulations of the Transport of Astrophysical Relativistic Jets in Magnetized Intergalactic Medium

Abstract: We present results from fully kinetic particle-in-cell simulations of the transport of astrophysical relativistic jets in magnetized intergalactic medium. As opposed to magnetohydrodynamic simulations, the results show that a strong charge-separation electric field, induced by the different responses between jet electrons and ions to the magnetic fields, significantly enhances the energy exchange between different species of charged particles and electromagnetic fields, thus playing a key role in determining t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…This also allowed us to simultaneously have a highly magnetized ambient plasma (with homogeneous and steady magnetic field) and a high-β piston (as can be seen in Table I, the plasma thermal β of the piston is β ther ≡ P ther /P mag ∼ 14.0). Moreover, since our magnetic field strength was more than two times higher, 40 reaching 20 T compared with the 8 T in Schaeffer et al, 32 we were able to decouple the electrons more strongly from the ions, 41 and the shock was able to fully separate from the piston, which is crucial for its characterization. 42 As a result, we have been able to characterize the plasma density and temperature, as well as the electric field developed at the shock front, and, more importantly, observe strong nonthermal accelerated proton populations for the first time.…”
Section: Introductionmentioning
confidence: 72%
“…This also allowed us to simultaneously have a highly magnetized ambient plasma (with homogeneous and steady magnetic field) and a high-β piston (as can be seen in Table I, the plasma thermal β of the piston is β ther ≡ P ther /P mag ∼ 14.0). Moreover, since our magnetic field strength was more than two times higher, 40 reaching 20 T compared with the 8 T in Schaeffer et al, 32 we were able to decouple the electrons more strongly from the ions, 41 and the shock was able to fully separate from the piston, which is crucial for its characterization. 42 As a result, we have been able to characterize the plasma density and temperature, as well as the electric field developed at the shock front, and, more importantly, observe strong nonthermal accelerated proton populations for the first time.…”
Section: Introductionmentioning
confidence: 72%
“…In recent years, scaled laboratory experiments [18][19][20] by particularly intense lasers have progressed rapidly, allowing us to have the abilities to quantitatively test the observations and models in an experimental setting where the initial and final states are well characterized. Astrophysical jets can be studied in a controlled environment using appropriately scaled laboratory experiments that reproduce and study critical physical aspects; even though laboratory-generated supersonic plasma jets and astrophysical jets have very different scales, they can have similar dimensionless hydrodynamic and magnetic field parameters and therefore can share common physical properties, as show in references [21][22][23][24][25][26][27][28][29][30]. In particular, both theoretical [31] and experimental [32,33] investigations have shown that a well-collimated astrophysical jet can be modeled by laser-produced plasmas in an external poloidal magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This also allowed us to simultaneously have a highly magnetized ambient plasma (with homogeneous and steady magnetic field) and a high-β piston (β ≡ P thermal /P mag is the ratio of the thermal pressure to the magnetic one). Moreover, since our magnetic field strength was more than two times higher 40 , reaching 20 T comparing to the 8 T in Schaeffer et al 33 , we were able to decouple more strongly the electrons from the ions 41 , and the shock was able to fully separate from the piston, which is crucial for its characterization 42 . As a result, we have been able to characterize the plasma density, temperature, as well as the E-field developed at the shock front, and more importantly, observe strong non-thermal accelerated proton populations for the first time.…”
Section: Introductionmentioning
confidence: 66%